Spectrum allocation with SINR guarantee for cognitive wireless multi-hop networks - Jie SUN; Wei GUO; Wei TANG (Tongxin xuebao)
To solve the problems inherent in fixed spectrum allocation wireless multi-hop networks such as channel collision,a full distributed spectrum allocation algorithm in‘underlay’fashion was proposed by using dynamic spectrum allocation technology in cognition radio,which was designed for wireless multi-hop networks formed with secondary users (SUs).This algorithm modeled the spectrum allocation problem as a static non-cooperative game,proofed the existence of Nash equilibrium (NE),and proposed an iterative algorithm to solve the NE.Extensive numerical experiments demonstrated that this algorithm can achieve the joint allocation of channels and power,and guarantee SUs’ signal to interference plus noise ratio(SINR)request while satisfying primary users’interference power limit.